Raw material composition of composite polyurethane foam plastic, composite polyurethane foam plastic as well as preparation method and application of composite polyurethane foam plastic

By using a composite polyurethane foam raw material composition of MIL-100 (Fe), white material and isocyanate, the problem of formaldehyde release in the production and natural aging of automobile accessories materials is solved, and the effects of high rebound rate, low hysteresis loss rate and low formaldehyde release are achieved. It is suitable for automotive interior accessories, improving the comfort performance and environmental protection of the materials.

CN119823561APending Publication Date: 2025-04-15BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
0 Cites 0 Cited by

Patent Information

Application Number
CN202510032060.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Polyurethane foaming materials for automotive accessories continue to release formaldehyde during production and natural aging, resulting in environmental pollution and health risks. It is difficult for the existing technology to effectively solve this problem.

Method used

A composite polyurethane foam raw material composition of MIL-100 (Fe), white material and isocyanate was used to prepare a composite polyurethane foam with high rebound rate, low hysteresis loss rate and low formaldehyde release through contact reaction and maturation process.

Benefits of technology

It effectively improves the rebound rate of composite polyurethane foam and reduces its formaldehyde emission during maturation and natural aging. It is suitable for automotive interior accessories, especially seat materials, and improves the comfort performance and environmental protection of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005234590650000121
    Figure BDA0005234590650000121
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane, and discloses a raw material composition of composite polyurethane foam plastic, the composite polyurethane foam plastic and a preparation method and application of the composite polyurethane foam plastic, and the raw material composition comprises MIL-100 (Fe), a white material and isocyanate. The raw material composition of the composite polyurethane foaming plastic provided by the invention can effectively improve the rebound rate of the prepared composite polyurethane foaming plastic, effectively reduces the hysteresis loss rate of the foaming plastic and the formaldehyde release amount in the curing and natural aging process, and is especially suitable for being applied to automotive interior accessories; the automobile seat cushion is particularly suitable for being applied to automobile seats.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane, and in particular to a raw material composition of composite polyurethane foam plastic, composite polyurethane foam plastic, and a preparation method and application thereof. Background Art

[0002] The foaming materials of auto parts have the problem of continuous formaldehyde release. Among them, polyurethane foaming materials are important materials in auto parts, and the amount used in seats alone can reach about 15kg. Auto parts foaming materials not only produce formaldehyde during the production process, but also continue to release formaldehyde under natural aging conditions. Therefore, the formaldehyde release problem of auto parts foaming materials needs to be solved urgently.

[0003] At present, in order to solve the problem of formaldehyde release from foaming materials of automobile parts, the existing technical solution is generally to add amine formaldehyde removers to the raw materials to inhibit the formaldehyde produced during the reaction process. However, this technical means cannot solve the problem of continuous formaldehyde release from foaming materials during the natural aging process.

[0004] The powder state of MOFs limits their practicality in industrial applications. MOFs are new crystalline porous materials that build periodic network structures through coordination bonds between metal ions or metal clusters and organic ligands under certain conditions. MIL-100(Fe) containing open coordinated unsaturated site carboxyl groups can effectively capture polar gases containing Lewis acids, providing the possibility of absorbing formaldehyde, but the currently synthesized MOFs are mostly polycrystalline powders, which are difficult to shape, making it difficult to achieve large-scale application in industrial fields. Summary of the invention

[0005] The present invention aims at the deficiencies of the prior art, and one of the technical problems to be solved is to provide a new raw material composition of composite polyurethane foam plastics, which can effectively improve the rebound rate of the prepared composite polyurethane foam plastics, and effectively reduce the hysteresis loss rate of the foam plastics and the release of formaldehyde during the maturation and natural aging processes. The raw material composition of the new composite polyurethane foam plastics is particularly suitable for application in automotive interior accessories, especially suitable for application in automotive seats.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a raw material composition of composite polyurethane foam plastics, the raw material composition comprising: MIL-100 (Fe), white material and isocyanate.

[0007] The second aspect of the present invention provides a method for preparing the composite polyurethane foam plastic of the present invention, using the raw material composition of the present invention to prepare the composite polyurethane foam plastic, the method comprising contacting and reacting the MIL-100 (Fe), white material and isocyanate, and aging.

[0008] The third aspect of the present invention provides a composite polyurethane foam plastic prepared by the preparation method of the present invention, wherein the mass content of the MIL-100 (Fe) is 0.01-10 wt % based on the total mass of the composite polyurethane foam plastic.

[0009] The fourth aspect of the present invention provides the use of the composite polyurethane foam plastic of the present invention in automobile interior accessories.

[0010] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0011] (1) The composite polyurethane foam plastic is prepared by the raw material composition of the composite polyurethane foam plastic of the present invention, which has a simple process, low cost, can be realized in large-scale industrial production, and has good industrial prospects;

[0012] (2) The composite polyurethane foam plastic is prepared by the raw material composition of the composite polyurethane foam plastic of the present invention, which can effectively improve the rebound rate of the prepared composite polyurethane foam plastic and effectively reduce the hysteresis loss rate of the foam plastic, and is applied to automobile seats to improve the comfort performance of the automobile seats;

[0013] (3) The composite polyurethane foam plastic is prepared by using the raw material composition of the composite polyurethane foam plastic of the present invention, which can effectively reduce the amount of formaldehyde released by the prepared composite polyurethane foam plastic during the ripening and natural aging process. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The specific embodiments of the present invention are described in detail below, but it should be pointed out that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.

[0016] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definitions in this specification shall prevail.

[0017] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those conventionally used in the art when the present invention was proposed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0018] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.

[0019] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.

[0020] The present invention provides a raw material composition of composite polyurethane foam plastics, the raw material composition comprising: MIL-100 (Fe), white material and isocyanate. The raw material composition of composite polyurethane foam plastics can effectively improve the resilience of the prepared composite polyurethane foam plastics, and effectively reduce the hysteresis loss rate of the foam plastics and the release of formaldehyde during the maturation and natural aging process, and is particularly suitable for application in automobile interior accessories, especially suitable for application in automobile seats.

[0021] In the present invention, the specific surface area of ​​the MIL-100 (Fe) can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the specific surface area of ​​the MIL-100 (Fe) is 500-2500m 2 / g, preferably 1500-2000m 2 / g, for example, 1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, etc. The raw material composition with the above-mentioned preferred specific surface area of ​​MIL-100 (Fe) can effectively reduce the release of formaldehyde during the maturation and natural aging process of the composite polyurethane foam.

[0022] In the present invention, the most probable pore size refers to the pore size with the highest probability of occurrence. The most probable pore size of the MIL-100 (Fe) can be selected in a wide range. The following is an exemplary description, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the most probable pore size of the MIL-100 (Fe) is 1-4 nm, preferably 2-3 nm. The raw material composition using the most probable pore size of the preferred MIL-100 (Fe) can effectively reduce the release of formaldehyde during the maturation and natural aging process of the composite polyurethane foam.

[0023] In the present invention, the MIL-100(Fe) having the aforementioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for the source of the MIL-100(Fe).

[0024] In the present invention, it can be known that the white material is a white material that can be used to prepare composite polyurethane foam plastics. The optional range of the white material is relatively wide. The following exemplary description does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the white material includes: polyether polyol, a cell opener, a cross-linking agent, a foaming agent, a catalyst and a foam stabilizer.

[0025] In the present invention, the type of isocyanate can be selected from a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the isocyanate is selected from toluene diisocyanate and / or diphenylmethane diisocyanate. The isocyanate described in the embodiment of the present invention uses diphenylmethane diisocyanate as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0026] In the present invention, the structural types of the polyether polyol can be selected from a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the polyether polyol is selected from polyether polyols whose polymerization units are one or more of ethylene oxide, propylene oxide and butylene oxide. In the embodiments of the present invention, the polyether polyols whose polymerization units are ethylene oxide and propylene oxide are used as examples to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0027] In the present invention, the initiator of the polyether polyol is generally a polyhydroxy compound: ethylene glycol, propylene glycol, 1,4-butanediol, glycerol, diethylene glycol, trihydroxymethylpropane, pentaerythritol, etc.; or a polyamine compound: ethylenediamine, toluenediamine, diaminodiphenylmethane, polymethylene polyphenyl polyamine, etc. The commercial product of the polyether polyol F3128 used in the embodiment of the present invention has glycerol as the initiator.

[0028] In the present invention, the number average molecular weight of the polyether polyol can be selected from a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the number average molecular weight of the polyether polyol is selected from 3000-8000 g / mol. The number average molecular weight of the polyether polyol described in the embodiment of the present invention is 5000 g / mol as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0029] In the present invention, the functionality of the polyether polyol refers to the number of terminal hydroxyl groups that can react in each polyether molecule. The functionality of the polyether polyol can be selected in a wide range. The following is an exemplary description, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the functionality of the polyether polyol is selected from 2 to 4. The functionality of the polyether polyol described in the examples of the present invention is 3 as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0030] In the present invention, the hydroxyl value of the polyether polyol can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the hydroxyl value of the polyether polyol is selected from 20-100 mgKOH / g, preferably 20-50 mgKOH / g, and more preferably 20-30 mgKOH / g. The hydroxyl value of the polyether polyol in the embodiment of the present invention is 29 mgKOH / g as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0031] In the present invention, the cell opener is used to increase the open cell rate of the prepared composite polyurethane foam and improve the foam performance. The types of the cell opener can be selected from a wide range. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the cell opener is selected from a polyether polyol whose polymerization units are mainly ethylene oxide.

[0032] In the present invention, the initiator of the polyether polyol such as ethylene oxide has been described above, generally a polyhydroxy compound: ethylene glycol, propylene glycol, 1,4-butanediol, glycerol, diethylene glycol, trihydroxymethylpropane, pentaerythritol, etc.; or a polyamine compound: ethylenediamine, toluenediamine, diaminodiphenylmethane, polymethylene polyphenyl polyamine, etc. The F5342 initiator used in the embodiment of the present invention is glycerol.

[0033] In the present invention, the number average molecular weight of the pore opening agent can be selected from a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the number average molecular weight of the pore opening agent is selected from 3000-8000 g / mol. The number average molecular weight of the pore opening agent in the embodiment of the present invention is 5000 g / mol as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0034] In the present invention, the functionality of the pore opener can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the functionality of the pore opener is selected from 2 to 4. The functionality of the pore opener in the embodiment of the present invention is 3 as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0035] In the present invention, the hydroxyl value of the pore opening agent can be selected in a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the hydroxyl value of the pore opening agent is selected from 20-150 mgKOH / g, preferably from 30-70 mgKOH / g, and more preferably from 30-40 mgKOH / g. The hydroxyl value of the pore opening agent in the embodiment of the present invention is 35.50-37.50 mgKOH / g as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0036] In the present invention, the cross-linking agent can be selected from a wide range of types, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the cross-linking agent is selected from polyols and / or organic amines, preferably selected from one or more of ethylene glycol, diethylene glycol, glycerol, 4,4'-methylenebis-2-chloroaniline, diethyltoluenediamine and triethanolamine, and more preferably selected from triethanolamine. The cross-linking agent in the embodiment of the present invention uses triethanolamine as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0037] In the present invention, the types of the foaming agent can be selected from a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the foaming agent is selected from one or more of water, C1-C5 alkanes and carbon dioxide, preferably water. The foaming agent in the embodiments of the present invention uses water as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0038] In the present invention, the catalyst can be selected from a wide range of types, which are exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the catalyst is selected from one or more organic amines, preferably one or more organic tertiary amines, and more preferably one or more of Evonik Chemical NE1050, NE1066, NE317, NE210, Huntsman ZF10, LE103 and Z130. The catalysts described in the embodiments of the present invention use Evonik Chemical NE1050 and NE210 as examples to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0039] In the present invention, NE1050 is a gel catalyst that promotes the gel reaction in the foaming process, promoting the reaction of isocyanate and polyether polyol. NE210 is a balance catalyst that plays a role in regulating the speed of foaming and gel reactions. In general use, the ratio of NE1050 to NE210 is (10-0.1):1. In the following specific embodiments, the ratio of NE1050 to NE210 is 1:1.

[0040] In the present invention, the foam stabilizer can be selected from a wide range of types. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the foam stabilizer is selected from one or more polyether-modified polysiloxanes, preferably selected from Dow Chemical VORASURF TM HR 8845 Additive 8845, VORASURF TM One or more of HR8845Additive8071, TF1348, Evonik Chemical 8742LO, 1107LO. The foam stabilizer in the embodiment of the present invention is Dow Chemical VORASURF TM HR 8845Additive 8845 is used as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0041] In the present invention, the amount of each substance in the raw material composition can be selected in a wide range. The following exemplary description is provided, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the mass ratio of the white material to the isocyanate is 1:(0.3-0.6), for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, etc., preferably 1:(0.32-0.38). The raw material composition with the above-mentioned preferred mass ratio of white material to isocyanate can effectively improve the resilience of the prepared composite polyurethane foam and effectively reduce the hysteresis loss rate of the foam, and can be applied to automobile seats to improve the comfort performance of automobile seats.

[0042] In the present invention, the mass ratio of the white material to MIL-100 (Fe) can be selected in a wide range. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the mass ratio of the white material to MIL-100 (Fe) is 100: (0.05-10), for example, 100: 0.05, 100: 0.1, 100: 0.5, 100: 1, 100: 2, 100: 3, 100: 4, 100: 5, 100: 6, 100: 7, 100: 8, 100: 9, 100: 10, etc., preferably 100: (0.5-3). The raw material composition with the above preferred mass ratio of white material to MIL-100 (Fe) can effectively reduce the release of formaldehyde in the prepared composite polyurethane foam during the maturation and natural aging process.

[0043] In the present invention, the dosage of each substance in the white material can be selected in a wide range. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, in the white material, the polyether polyol is 80-100 parts, preferably 88-94 parts, the cell opener is 1.5-4.0 parts, preferably 1.6-2.4 parts, the cross-linker is 0.3-2.0 parts, preferably 0.8-1.2 parts, the foaming agent is 1.0-5.0 parts, preferably 2.5-3.3 parts, the catalyst is 0.5-2.5 parts, preferably 0.8-1.2 parts, and the foam stabilizer is 0.3-1.5 parts, preferably 0.6-1.2 parts. The raw material composition composed of the dosage of each substance in the above-mentioned preferred white material can effectively improve the rebound rate of the prepared composite polyurethane foam plastic and effectively reduce the hysteresis loss rate of the foam plastic. When applied to automobile seats, the comfort performance of automobile seats can be improved.

[0044] The raw material compositions with the above characteristics of the present invention can achieve the purpose of the present invention. There is no special requirement for the method for preparing the composite polyurethane foam plastic. The following exemplary description is not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the present invention provides a method for preparing a composite polyurethane foam plastic. The composite polyurethane foam plastic is prepared by using the raw material composition of the present invention. The method comprises contacting and reacting the MIL-100 (Fe), white material and isocyanate, and aging. The composite polyurethane foam plastic is prepared by using the raw material composition of the composite polyurethane foam plastic of the present invention. The process is simple, the cost is low, and large-scale industrial production can be achieved, which has good industrial prospects.

[0045] According to a preferred embodiment of the present invention for preparing composite polyurethane foam, the method comprises:

[0046] I. Mix the white material with MIL-100 (Fe);

[0047] II. Add isocyanate to step (1) for contact reaction and ripening.

[0048] In the present invention, there is no special requirement for the mixing method, as long as uniform mixing is achieved. Conventional mixing methods in the art can achieve the purpose of the present invention, such as mechanical stirring mixing.

[0049] In the present invention, there is no special requirement for the rotation speed of the mechanical stirring and mixing. The conventional mechanical stirring and mixing rotation speed in the art can achieve the purpose of the present invention. For example, it is generally 2000-3000rpm. The rotation speed of the mechanical stirring and mixing in the embodiment of the present invention is 2500rpm as an example to illustrate the advantages of the present invention, but it does not limit the scope of the present invention.

[0050] In the present invention, there is no special requirement for the mixing temperature. The conventional mixing temperature in the art can achieve the purpose of the present invention, for example, it is generally 25-50°C. The mixing temperature in the embodiments of the present invention takes 25°C as an example to illustrate the advantages of the present invention, but does not limit the scope of the present invention.

[0051] In the present invention, there is no special requirement for the mixing time, which is adjusted according to the mixing temperature and rotation speed, for example, generally 1-10 minutes. The mixing time in the embodiments of the present invention is 1 minute as an example to illustrate the advantages of the present invention, but it does not limit the scope of the present invention.

[0052] In the present invention, there is no special requirement for the contact reaction method, and any conventional contact reaction method in the art can be used in the present invention. In order to fully react and ensure the accuracy and consistency of the product, the contact reaction is generally carried out in a mold. For example, in the embodiment of the present invention, the mixture is first stirred at 25° C. for uniform contact, and then poured into the mold for contact reaction. The above is an exemplary description, but does not limit the scope of the present invention.

[0053] In the present invention, the conditions of the contact reaction can be selected in a wide range, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the temperature of the contact reaction is 15-70° C., for example, 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., etc., preferably 50-70° C. The temperature of the contact reaction in the embodiment of the present invention is 65° C. as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0054] In the present invention, there is no special requirement for the rotation speed of the contact reaction, which is consistent with the rotation speed requirement for mechanical stirring and mixing, and will not be described in detail here.

[0055] In the present invention, there is no special requirement for the contact reaction time, which is specifically adjusted according to the temperature and rotation speed of the contact reaction, for example, generally 1-10 minutes. The contact reaction time in the embodiment of the present invention is 3 minutes as an example to illustrate the advantages of the present invention, but it does not limit the scope of the present invention.

[0056] In the present invention, the aging is to promote the internal reaction of the composite polyurethane foam to continue fully, to ensure that the structure and size of the foam are stable, and not deformed or collapsed. The aging conditions can be selected in a wide range, and the following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the aging temperature is 15-30°C, for example, 15°C, 17°C, 19°C, 21°C, 23°C, 25°C, 27°C, 29°C, 30°C, etc., preferably 20-30°C. The aging temperature in the embodiment of the present invention is 23°C as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto.

[0057] In the present invention, there is no special requirement for the aging time, which is adjusted according to the aging temperature, for example, generally 1-48 hours, preferably 1-24 hours. The aging time in the embodiment of the present invention is 24 hours as an example to illustrate the advantages of the present invention, but it does not limit the scope of the present invention.

[0058] In the present invention, there is no special requirement for the aging method, and conventional aging methods in the art can be used in the present invention, for example, aging in a dark and ventilated environment is generally used.

[0059] The present invention provides a composite polyurethane foam plastic prepared by the preparation method of the present invention, wherein the mass content of the MIL-100 (Fe) is 0.01-10wt% based on the total mass of the composite polyurethane foam plastic. The composite polyurethane foam plastic prepared by the preparation method of the present invention has the characteristics of high rebound rate, low hysteresis loss rate, low formaldehyde release during maturation and natural aging, etc.

[0060] In the present invention, the formaldehyde release concentration of the composite polyurethane foam plastic after aging for 24 hours can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the formaldehyde release concentration of the composite polyurethane foam plastic after aging for 24 hours is ≤45μg / m 3 , preferably 20-40 μg / m 3 , for example, 20 μg / m 3 , 25 μg / m 3 , 30 μg / m 3 , 35 μg / m 3 40 μg / m 3The raw material composition of the composite polyurethane foam plastic of the present invention is used to prepare the composite polyurethane foam plastic, which can effectively reduce the release of formaldehyde in the aging process of the prepared composite polyurethane foam plastic.

[0061] In the present invention, the formaldehyde release concentration of the composite polyurethane foam plastic after natural aging for 30 days refers to the concentration of formaldehyde released by the composite polyurethane foam plastic after being placed for 30 days under the conditions of 25°C and normal pressure. The formaldehyde release concentration of the composite polyurethane foam plastic after natural aging for 30 days can be selected in a wide range. The following exemplary description is provided, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the formaldehyde release concentration of the composite polyurethane foam plastic after natural aging for 30 days is ≤60μg / m 3 , preferably 20-40 μg / m 3 , for example, 20 μg / m 3 , 25 μg / m 3 , 30 μg / m 3 , 35 μg / m 3 40 μg / m 3 The raw material composition of the composite polyurethane foam plastic of the present invention is used to prepare the composite polyurethane foam plastic, which can effectively reduce the release of formaldehyde in the prepared composite polyurethane foam plastic during the natural aging process.

[0062] In the present invention, the resilience of the composite polyurethane foam refers to the measure of the ability of the material to recover its original shape after being subjected to an external force. The resilience of the composite polyurethane foam can be selected in a wide range. The following exemplary description is provided, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the resilience of the composite polyurethane foam is 50-65%, for example, 50%, 53%, 55%, 58%, 60%, 63%, 65%, etc. The raw material composition of the composite polyurethane foam of the present invention is used to prepare the composite polyurethane foam, which can effectively improve the resilience of the prepared composite polyurethane foam.

[0063] In the present invention, the hysteresis loss rate of the composite polyurethane foam plastic refers to the ratio of the work lost when the test piece is stretched and then contracted by an external force to the work required for the original extension. The hysteresis loss rate of the composite polyurethane foam plastic can be selected in a wide range. The following exemplary description is not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the hysteresis loss rate of the composite polyurethane foam plastic is 15-25%, for example, 15%, 17%, 20%, 23%, 25%, etc. The raw material composition of the composite polyurethane foam plastic of the present invention is used to prepare the composite polyurethane foam plastic, which can effectively reduce the hysteresis loss rate of the composite polyurethane foam plastic.

[0064] Accordingly, the present invention provides the use of the composite polyurethane foam plastic of the present invention in automobile interior accessories. Preferably, the automobile interior accessories include one or more of automobile seats, carpets and front surrounds.

[0065] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0066] (1) The composite polyurethane foam plastic is prepared by the raw material composition of the composite polyurethane foam plastic of the present invention, which has a simple process, low cost, can be realized in large-scale industrial production, and has good industrial prospects;

[0067] (2) The composite polyurethane foam plastic is prepared by the raw material composition of the composite polyurethane foam plastic of the present invention, which can effectively improve the rebound rate of the prepared composite polyurethane foam plastic and effectively reduce the hysteresis loss rate of the foam plastic, and is applied to automobile seats to improve the comfort performance of the automobile seats;

[0068] (3) The composite polyurethane foam plastic is prepared by using the raw material composition of the composite polyurethane foam plastic of the present invention, which can effectively reduce the amount of formaldehyde released by the prepared composite polyurethane foam plastic during the ripening and natural aging process.

[0069] The present invention will be described in detail by way of examples below. In the following examples, the polyether polyol is a commercial product of Wanhua Chemical Group Co., Ltd. with a brand name of polyether polyol F3128, a molecular weight of 5000 g / mol, a functionality of 3, a hydroxyl value of 29 mgKOH / g, and a starting agent of glycerol; the pore opening agent is a commercial product of Wanhua Chemical Group Co., Ltd. with a brand name of polyether polyol F5342, a molecular weight of 5000 g / mol, a functionality of 3, a hydroxyl value of 35.50-37.50 mgKOH / g, and a starting agent of glycerol; the crosslinking agent is a commercial product of triethanolamine with a purity of 98% produced by Shandong Hongyuansheng New Materials Technology Co., Ltd.; the foaming agent is water; the catalyst is a commercial product of Evonik Chemical (Shanghai) Co., Ltd. with a brand name of NE1050 and NE2100; the foam stabilizer is a silicone oil VORASURF produced by Dow Chemical (Shanghai) Co., Ltd. TMHR 8845Additive 8845 is a commercial product; the mass content of MIL-100(Fe) is calculated by feeding; the formaldehyde release concentration after aging for 24 hours and the formaldehyde release concentration after natural aging for 30 days are measured by the high-temperature 100L bag method (100L bag method test conditions: put the foamed sample into a 100L Tedlar sampling bag, fill it with high-purity nitrogen with a volume of about 30L, then extract the gas, repeat this step twice, and then accurately add 50L of high-purity nitrogen to the sampling bag, and then put it into a bag that has been stabilized at (65±1) ℃ in an oven with a humidity of 50±10% RH, and after 2h±10min, the gas is captured by a DNPH tube and then analyzed by HPLC to obtain the formaldehyde emission concentration); the resilience of the composite polyurethane foam plastic is calculated by a falling ball rebound tester test (measured using test method A in "GB / T6670-2008 Determination of rebound properties of soft foam polymer materials by falling ball method"); the hysteresis loss rate of the composite polyurethane foam plastic is calculated by a universal testing machine test (test basis is "GB / T 33609-2017, Test method for hysteresis loss of soft foam polymer materials").

[0070] Example 1

[0071] 1) At 25°C, 92 parts of polyether polyol, 2 parts of cell opener, 1 part of crosslinker, 3 parts of foaming agent, 0.8 parts of catalyst (0.4 parts of NE1050, 0.4 parts of NE210) and 1.2 parts of foam stabilizer were stirred and mixed at a mechanical stirrer speed of 2500 rpm for 1 min to obtain a white material, and then 1 part of MIL-100 (Fe) (specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3 nm) and continue stirring and mixing for 1 min;

[0072] 2) At 25°C, 37 parts by mass of diphenylmethane diisocyanate were added to step 1), stirred for 8 seconds at a speed of 2500 rpm using a mechanical stirrer, poured into a mold at a mold temperature of 65°C and reacted for 3 minutes, and then aged for 24 hours in a dark and ventilated environment at a temperature of 23°C to obtain a composite polyurethane foam plastic. The formaldehyde release concentration after aging for 24 hours was monitored, and the test results are shown in Table 1.

[0073] The above composite polyurethane foam plastic was further aged naturally for 30 days, and the formaldehyde release concentration during the natural aging process of 30 days (natural aging for 30 days in ambient air, environmental conditions: temperature: 23±2°C, humidity: 50±10%RH) was monitored. The test results are shown in Table 1.

[0074] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0075] Example 2

[0076] The method and steps of Example 1 were followed, except that 0.05 parts by mass of MIL-100 (Fe) (with a specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0077] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0078] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0079] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0080] Example 3

[0081] The method and steps of Example 1 were followed, except that 0.1 parts by mass of MIL-100 (Fe) (with a specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0082] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0083] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0084] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0085] Example 4

[0086] The method and steps of Example 1 were followed, except that 0.5 parts by mass of MIL-100 (Fe) (with a specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0087] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0088] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0089] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0090] Example 5

[0091] The method and steps of Example 1 were followed except that 2 parts by mass of MIL-100 (Fe) (with a specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0092] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0093] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0094] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0095] Example 6

[0096] The method and steps of Example 1 were followed, except that 3 parts by mass of MIL-100 (Fe) (with a specific surface area of ​​1670 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0097] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0098] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0099] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0100] Example 7

[0101] The method steps of Example 1 were followed, except that 40 parts by mass of diphenylmethane diisocyanate was added to prepare the composite polyurethane foam.

[0102] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0103] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0104] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0105] Example 8

[0106] The method steps of Example 1 were followed, except that 30 parts by mass of diphenylmethane diisocyanate was added to prepare a composite polyurethane foam.

[0107] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0108] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0109] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0110] Example 9

[0111] The method and steps of Example 1 were followed, except that 1 part by mass of MIL-100 (Fe) (with a specific surface area of ​​1000 m 2 / g, the most probable pore size is 2.3nm) to prepare a composite polyurethane foam.

[0112] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0113] The above composite polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0114] The above composite polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0115] Comparative Example 1

[0116] The polyurethane foam was prepared according to the method steps of Example 1, except that MIL-100(Fe) was not added.

[0117] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0118] The polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0119] The above polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0120] Comparative Example 2

[0121] The polyurethane foam was prepared according to the method steps of Example 1, except that 1 part by mass of diethylenetriamine was used instead of MIL-100(Fe).

[0122] The formaldehyde release concentration during the 24h ripening process was monitored, and the test results are shown in Table 1.

[0123] The polyurethane foam plastic was further aged for 30 days, and the formaldehyde release concentration during the 30-day natural aging process was monitored. The test results are shown in Table 1.

[0124] The above polyurethane foam plastics were tested for rebound rate and hysteresis loss rate performance, and the test results are shown in Table 2.

[0125] Table 1

[0126] Example <![CDATA[Formaldehyde release concentration after 24 hours of curing (μg / m 3 )]]> <![CDATA[Formaldehyde release concentration after 30 days of natural aging (μg / m 3 )]]> Example 1 32.03 27.78 Example 2 43.01 58.13 Example 3 41.59 50.49 Example 4 39.78 33.27 Example 5 23.25 25.26 Example 6 25.68 28.72 Example 7 29.86 24.33 Example 8 40.25 49.26 Example 9 41.85 51.31 Comparative Example 1 87.69 93.70 Comparative Example 2 46.95 102.46

[0127] It can be seen from the results in Table 1 that the composite polyurethane foam plastic prepared by using the raw material composition of the present invention can not only effectively reduce the formaldehyde generated in the foam plastic production process, but also effectively reduce the continuous release of formaldehyde in the natural aging process.

[0128] Table 2

[0129]

[0130]

[0131] It can be seen from the results in Table 2 that the composite polyurethane foam plastic prepared by using the raw material composition of the present invention can effectively improve the rebound rate of the prepared composite polyurethane foam plastic and effectively reduce the hysteresis loss rate of the foam plastic, and can be applied to car seats to improve the comfort performance of car seats.

[0132] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A raw material composition for composite polyurethane foam, characterized in that: The raw material composition comprises: MIL-100(Fe), white material and isocyanate.

2. The raw material composition according to claim 1, characterized in that The specific surface area of ​​the MIL-100 (Fe) is 500-2500 m 2 / g, preferably 1500-2000m 2 / g; and / or The most probable pore size of the MIL-100(Fe) is 1-4 nm, preferably 2-3 nm; and / or The white material comprises: polyether polyol, a cell opener, a cross-linking agent, a foaming agent, a catalyst and a foam stabilizer; and / or The isocyanate is selected from toluene diisocyanate and / or diphenylmethane diisocyanate.

3. The raw material composition according to claim 2, characterized in that The polyether polyol is selected from polyether polyols whose polymerization units are one or more of ethylene oxide, propylene oxide and butylene oxide; and / or The number average molecular weight of the polyether polyol is selected from 3000-8000 g / mol; and / or The functionality of the polyether polyol is selected from 2-4; and / or The hydroxyl value of the polyether polyol is selected from 20-100 mgKOH / g, preferably selected from 20-50 mgKOH / g, and more preferably selected from 20-30 mgKOH / g; and / or The cell opener is selected from polyether polyols whose polymerization units are ethylene oxide; and / or The number average molecular weight of the pore opener is selected from 3000-8000 g / mol; and / or The functionality of the cell opener is selected from 2-4; and / or The hydroxyl value of the pore opening agent is selected from 20-150 mgKOH / g, preferably selected from 30-70 mgKOH / g, and more preferably selected from 30-40 mgKOH / g; and / or The cross-linking agent is selected from polyols and / or organic amines, preferably selected from one or more of ethylene glycol, diethylene glycol, glycerol, 4,4'-methylenebis-2-chloroaniline, diethyltoluenediamine and triethanolamine, more preferably selected from triethanolamine; and / or The foaming agent is selected from one or more of water, C1-C5 alkanes and carbon dioxide, preferably water; and / or The catalyst is selected from one or more organic amines, preferably one or more organic tertiary amines, more preferably one or more NE1050, NE1066, NE317, NE210, ZF10, LE103 and Z130; and / or The foam stabilizer is selected from one or more polyether-modified polysiloxanes, preferably VORASURF TM HR 8845 Additive 8845, VORASURF TM One or more of HR 8845 Additive 8071, TF1348, 8742LO, 1107LO.

4. The raw material composition according to claim 1 or 2, characterized in that The mass ratio of the white material to the isocyanate is 1:(0.3-0.6), preferably 1:(0.32-0.38); and / or The mass ratio of the white material to MIL-100 (Fe) is 100:0.05-10, preferably 100:0.5-3.

5. The raw material composition according to claim 2 or 3, characterized in that: In parts by mass, in the white material, The polyether polyol is 80-100 parts, preferably 88-94 parts; and / or The cell opening agent is 1.5-4.0 parts, preferably 1.6-2.4 parts; and / or The cross-linking agent is 0.3-2.0 parts, preferably 0.8-1.2 parts; and / or The foaming agent is 1.0-5.0 parts, preferably 2.5-3.3 parts; and / or The catalyst is 0.5-2.5 parts, preferably 0.8-1.2 parts; and / or The foam stabilizer is 0.3-1.5 parts, preferably 0.6-1.2 parts.

6. A method for preparing a composite polyurethane foam, characterized in that: The composite polyurethane foam is prepared by using the raw material composition according to any one of claims 1 to 5, the method comprising: The MIL-100(Fe), white material and isocyanate are contacted and reacted, and then aged.

7. The preparation method according to claim 6, characterized in that: The method includes: I. Mix the white material with MIL-100 (Fe); II. adding the isocyanate to the step (1) for contact reaction and aging; Preferably, The conditions of the contact reaction include: The temperature is: 15-70°C, preferably: 50-70°C; and / or The ripening conditions include: The temperature is: 15-30°C, preferably: 20-30°C.

8. The composite polyurethane foam obtained by the preparation method according to claim 6 or 7, characterized in that: Based on the total mass of the composite polyurethane foam plastic, the mass content of the MIL-100 (Fe) is 0.01-10wt%.

9. The composite polyurethane foam according to claim 8, characterized in that The formaldehyde release concentration of the composite polyurethane foam plastic after aging for 24 hours is ≤45 μg / m 3 , preferably 20-40 μg / m 3 ; and / or The formaldehyde release concentration of the composite polyurethane foam plastic after natural aging for 30 days is ≤60 μg / m 3 , preferably 20-40 μg / m 3 ; and / or The resilience of the composite polyurethane foam is 50-65%; and / or The hysteresis loss rate of the composite polyurethane foam is 15-25%.

10. Use of the composite polyurethane foam plastic according to claim 8 or 9 in automobile interior accessories, characterized in that: The automobile interior accessories include one or more of automobile seats, carpets and front surrounds.